Laparoskopska hernioplastika ventralnih kil - Vrbanec, Borislav (Endoskopska revija, 2006)
Background. Laparoscopy has been increasingly considered the therapy of choicein the management of ventral hernia. The paper presents our results and experience with this modern minimally invasive approach to the treatment of ventra hernias. Patients and Methods. Twenty-nine patients, aged 40 - 82 years(mean 58.4 yrs) were enrolled in the study. The male to female ratio was 1:3. Umbilical hernia was diagnosed in 55% of the patients, hernia after lowermedian laparotomy in 25%, hernia after upper median laparotomy and appendectomy in 10%, and hernia after pararectal laparotomy in 5%. All patients were operated on under general anaesthesia. Results. The mean operative time was 70 minutes. A perforation in a female patient, who had a serosal lesion rnanaged by laparoscopic suture closure, was repaired via laparotomy. Seroma formation was observed in four male patients, one female patient developed a haematoma in the hernial sac, and orne had recurrence eighteen months after surgery. Conclusion. We believe that laparoscopic repairof ventral hernias is superior to open surgery: it affords better visualization of the abdominal wall, and is associated with faster recovery and lower recurrence rates. Laparoscopic management, however, is costly and should therefore be reserved for strictly selected cases.
Keywords: Hernia, Ventral; Hernija ventralna; Laparoskopija; Surgery; Laparoscopy; Zdravljenje, izid; Treatment Outcome; kila; kirurško zdravljenje; laparoskopska kirurgija